Influência do ambiente, da embalagem e do período de armazenamento na qualidade fisiológica de sementes de girassol e gergelim. - Lima, Denise de Castro (2012)
Seeds stored in improper conditions have reduced germination and vigor, this entails low percentage of field emergence, compromising crop development. In seed storage, many factors can affect the physiological quality of seeds, among which we can highlight: the environmental conditions of the storage location, the type of packaging used in the packaging of the seeds and the duration of storage. The work was developed with the objective to monitor the viability of sunflower seeds and sesame seeds stored in different environments and packaging in order to preserve. This research was developed in the Laboratory of Seed Analysis from the Department of Plant Science, Federal University of Ceará-UFC, in Fortaleza, in the year 2011. At the beginning of the experiment was made an initial assessment of the material by determining the water content and germination, first count, accelerated aging, speed of emergence and seedling dry weight. The seeds were packed in paper bag, multiwall paper, and black polyethylene plastic bottle and stored for a period of twelve months in different environments: a cold room (10 ° C and 45% UR) at ambient conditions of Fortaleza, refrigerator (4 ° C) and freezer (-20 ° C). The experiments were conducted in a completely randomized design in a split plot design scheme. In the main plots were allocated storage environments (A1= environmental condition, A2 = cold, A3 = fridge and A4 = freezer), subplots packaging (E1= paper bag, E2 = multiwall paper bag, E3 = polyethylene black and E4 = pet bottle) and in the subsubplot the storage periods (P1 = initial, P2 = 3 months, P3= 6 months, P4 = 9 months and P5= 12 months). When I finish the work we concluded that the environments of cold, fridge and freezer are most suitable for the storage of sunflower seeds, regardless of the type of packaging used, and sunflower seeds stored under natural conditions lose viability. From the third month of storage, regardless of the type of packaging. For the sesame seeds in a cold environment and the refrigerator are the most suitable for the storage of these seeds, regardless of the type of packaging used, and when stored under natural seeds remain viable for up to six months of storage. In the environment of the freezer paper package is the most suitable for the packaging of sesame seeds.